PERSEPSI WAJIB PAJAK MENGENAI KORUPSI PAJAK DAN PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK (Studi pada WPOP yang Menjalankan Usaha di KPP Pratama Malang Utara) - Suciaty, Suciaty (Jurnal Mahasiswa Perpajakan, 2014)
Tax has an important role in Indonesia, considering the government's national development requires a relatively large funds. The taxation system in Indonesia are demanding Taxpayers active in fulfilling the obligation of taxation, thus requiring a high compliance. The purpose of this research is to know the influence of simultaneous and partial Taxpayer perceptions about tax corruption on mass media and law enforcement of tax corruption against Taxpayers compliance, and to know the variables that influence dominant. The kind of this research using a explanatory research. Sample research used is Private Taxpayers who are running Businesess and registered in KPP Pratama Malang Utara. Sampling techniques using accidental sampling. Method of analysis used is descriptive analysis and multiple linear analysis. Based on the research that has been done, the simultaneous perception of taxpayers with a variable tax corruption on mass media and law enforcement of tax corruption had a significant influence to Taxpayer compliance. Tax corruption on mass media had a significant influence on partial variables of Taxpayer compliance, while variable law enforcement of tax corruption had no significant influence on partial to Taxpayers compliance. Tax corruption on mass media is the dominant variable influence on Taxpayer compliance. Keywords: Taxpayers perception, Tax corruption, Taxpayer compliance